Establishment of an Accelerated Doctor of Family Medicine Program at Unaizah College of Medicine, Qassim University, Kingdom of Saudi Arabia. (January 2019) - Al-Shafei, Ahmad; Al-Damegh, Saleh; Al-Matham, Fahad; Al-Mohaimeed, Abdulrahman; Al-Nafeesah, Abdullah; Hamad-Aldosary, Ahmad; Al-Otaibi, Moteb; Al Wutayd, Osama; Mansour, Ali; El-Gendy, Ola; Fadda, Walaa; El-Migdadi, Fayig; et al.
Primary health care is well known to be the cornerstone for the health of the society. Furthermore, efficient health care at the secondary and tertiary levels is entirely dependent on effective primary health care. The Kingdom of Saudi Arabia (KSA) is currently building up a rigorous primary health care system with a large number of well-equipped primary health care centers. However, there is an acute shortage of Saudi family physicians throughout the country; both in urban and rural areas. There is no evidence in the literature supporting the relatively long 7 years' traditional duration of medical programs in the KSA. Rather, several US and Canadian medical schools have established accelerated programs in Internal Medicine and Family Medicine with graduates comparable with those of the traditional curricula in terms of standardized tests, initial resident characteristics, and performance outcomes. In response to the challenges the KSA is facing in primary health care, Unaizah College of Medicine at Qassim University is proposing to establish an accelerated Doctor of Family Medicine Program that would run for total duration of 6 years. Herein, we describe a concise outline of this program.